KNOWLEDGE, ATTITUDE AND PRACTICES OF INTENSIVE CARE UNIT NURSES ABOUT PHYSICAL RESTRAINT AT TERTIARY CARE HOSPITAL LAHORE - REHMAN, NU; SADDIQUE, H (Biological and Clinical Sciences Research Journal, 2024)
Physical restraint is a common intervention in intensive care units (ICUs) to ensure patient safety and prevent harm. However, its inappropriate use poses ethical and clinical challenges, particularly in resource-constrained healthcare systems like Pakistan. Objective: To assess the knowledge, attitudes, and practices of ICU nurses regarding physical restraint in a tertiary care hospital in Lahore, Pakistan. Methods: A descriptive cross-sectional study was conducted among 137 ICU nurses using a structured questionnaire. The data were analyzed using SPSS version 26, with results presented as frequencies and percentages. Results: The study revealed that 47.1% of nurses demonstrated moderate knowledge of physical restraint, while 33.1% exhibited good knowledge. Attitudes were mixed, with 52.2% displaying positive attitudes and 47.8% exhibiting negative attitudes. Good practices were reported by 61.8% of nurses, whereas 38.2% showed poor adherence to recommended protocols. Nurses with higher qualifications and greater experience demonstrated significantly better knowledge and practices. Conclusion: Despite moderate knowledge and adherence to some practices, gaps in attitudes and inconsistent protocol adherence remain challenges in ICU settings. Targeted education, institutional support, and clear policies are essential to enhance nurses’ competency in the ethical and effective use of physical restraints.